2016
DOI: 10.1038/srep39063
|View full text |Cite
|
Sign up to set email alerts
|

Bell’s Nonlocality Can be Detected by the Violation of Einstein-Podolsky-Rosen Steering Inequality

Abstract: Recently quantum nonlocality has been classified into three distinct types: quantum entanglement, Einstein-Podolsky-Rosen steering, and Bell’s nonlocality. Among which, Bell’s nonlocality is the strongest type. Bell’s nonlocality for quantum states is usually detected by violation of some Bell’s inequalities, such as Clause-Horne-Shimony-Holt inequality for two qubits. Steering is a manifestation of nonlocality intermediate between entanglement and Bell’s nonlocality. This peculiar feature has led to a curious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
31
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 55 publications
5
31
0
2
Order By: Relevance
“…It should be noted that the entanglement is not only one kind of quantum correlations. At this point, we can mention quantum discord [33][34][35] , quantum steering [36][37][38][39] , and Bell non-locality [40,41] .…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the entanglement is not only one kind of quantum correlations. At this point, we can mention quantum discord [33][34][35] , quantum steering [36][37][38][39] , and Bell non-locality [40,41] .…”
Section: Introductionmentioning
confidence: 99%
“…Although they are not equivalent [ 1 , 2 , 3 , 4 ], they are closely inter-related. On the one hand, there is a hierarchal structure of three types of nonclassical correlation/nonlocality represented by these three aspects [ 2 , 5 ]. Bell nonlocality refers to the strongest type of quantum correlation that cannot be reproduced by using any local hidden variable (LHV) model.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the data-processing inequality for an extended Rényi relative entropy, Zhu et al [ 41 ] introduced a family of steering inequalities, which detect steering much more efficiently than those inequalities known before. Chen et al [ 42 ] showed that Bell nonlocal states can be constructed from some steerable states. Furthermore, a nine-setting steering inequality had also been presented for developing more efficient one-way steering and detecting some Bell nonlocal states.…”
Section: Introductionmentioning
confidence: 99%